(untitled) (Journal of Economic Research & Business Administration, 2016)
The article deals with ways to improve the management level of venture service activities on public support for this kind of business consideration of this issue due to the fact that venture capital industry cannot develop without government support. Business venture as a stimulating mechanism of innovation based economy.